Bilateral thalamic stroke due to occlusion of the artery of Percheron: A case report and literature review - Eliz Achhami; Seshkanta Lamichhane; Satyam Mahaju; Lukash Adhikari; Ashim Kandel; Anubhav Poudel (Clinical Case Reports, 2023)
Abstract Bilateral thalamic infarction resulting from the occlusion of the artery of Percheron (AOP) is a rare cerebrovascular event with distinctive clinical presentations. This case report explores the intricate relationship between vascular anatomy, midbrain function, and clinical manifestations. A 48‐year‐old male farmer with a history of diabetes mellitus presented with sudden‐onset visual disturbances, diplopia, bilateral eyelid drooping, and loss of consciousness. Extensive evaluations, including advanced imaging techniques, led to the diagnosis of bilateral upper midbrain infarction involving AOP. This case underscores the complexity of neurovascular interactions, highlighting the importance of precise diagnosis, and tailored management in addressing rare cerebrovascular conditions.